University Brand Equity and Decision Making Processes for Admission to Private Universities of Students in Bangkok and Metropolitan Area - เอียดงามสม, มณีรัตน์; วิวัฒนชาต, ศศนันท์ (Journal of Humanities and Social Sciences, Rajapruk University, 2020)
The purposes of this research were to: 1) study the demographic student that decision to entrance in private universities in Bangkok Metropolitan, 2) study decision making process of students to entrance in private universities in Bangkok Metropolitan Region, 3) study the level of university brand equity for decision making for further study in the private universities, 4) compare the decision making process to study in private universities by personal factors, 5) compare the brand equity for decision making for further study in the private universities by personal factors and 6) study the relationships between the university brand equity and decision making. The respondent in the research were 400 students, selected through simple random sampling. The questionnaire used for collected data. Data were analyzed by descriptive statistics, frequency, percentage, mean, standard deviation, t-test, One-way ANOVA and Pearson's correlation analysis. The results of the research revealed that: 1) the students most female. The average age of the students who were studying at the third and second year was between 21 - 25 years old. Their income per month between 10,001 - 15,000 Baht, 2) the decision making process of students to entrance in private universities in Bangkok Metropolitan Region were rated at a high level, 3) the opinions towards the university brand equity were rated at a high level, 4) the students who were different in occupation and income per month had difference decision making process to study in private universities at .05 significantly, 5) the students who were different in occupation and income had difference brand equity for decision making for further study in the private universities at .05 significantly, 6) the relationships between the university brand equity and decision making to study at private universities in Bangkok Metropolitan Region were in accordance to at a high level as a whole.